Comparison of corneal endothelial cell density and morphology after posterior chamber phakic intraocular lens implantation with and without a central hole. Issue 11 (14th March 2017) - Goukon, Hiroyasu; Kamiya, Kazutaka; Shimizu, Kimiya; Igarashi, Akihito
Abstract : Aim: To compare the corneal endothelial cells after posterior chamber phakic intraocular lens with and without a central hole (hole implantable collamer lens (ICL) and conventional ICL) implantation for the correction of moderate to high myopia. Methods: This retrospective study evaluated 34 eyes of 34 patients who underwent hole ICL implantation and 25 eyes of 25 patients who underwent conventional ICL implantation. Preoperatively and 3 months, and 1 and 2 years postoperatively, we compared the central corneal endothelial cell density (ECD), coefficient of variation in cell size (CV) and the percentage of hexagonal cells (HEX) between the two groups using a non-contact specular microscope (EM-3000, Tomey). Preoperatively and 2 years postoperatively, we also compared them in the peripheral regions. Results: The mean central ECD loss was 0.3% and 1.1%, 2 years after hole ICL and conventional ICL implantation, respectively (Mann-Whitney U test, p=0.72). There were no significant changes in central ECD, CV or HEX at any time points either after hole ICL or conventional ICL implantation, and a significant decrease only in terms of ECD in the superior regions after conventional ICL implantation. Conclusions: Both ICLs do not induce a significant change in the density, polymegethism or polymorphism of corneal endothelial cells even 2 years postoperatively, except for the density in the superior regions after conventional ICL implantation. However, hole ICL implantation may have advantages over conventional ICL implantation only in terms of the density in the superior regions, possibly because preoperative laser iridotomies are unnecessary.